Correlation between serum and salivary phenytoin drug metabolite levels to phenytoin influenced gingival overgrowth in adult male subjects. A prospective cohort study - Sridharan, Srirangarajan; Priyanka, S. (International Journal of Epilepsy, 2017)
Background To correlate serum and salivary phenytoin drug metabolite levels in males to phenytoin influenced gingival overgrowth (PIGO).Methods Thirty male patients who are to start with oral phenytoin therapy were recruited. Plaque index (PI), Gingival index (GI), and Oral hygiene index (OHI) were recorded. Basic periodontal therapy was performed. Patients were followed up at 3, 6, 9 and 12 months intervals. Based on the gingival status they were divided in to two groups; Group1 (responders) and Group 2 (non responders). Serum and Salivary samples were analyzed for the drug metabolite levels spectophotometrically.Results The mean values of phenytoin drug metabolite levels in serum of group 1 and group 2 subjects were 14.5 ± 2.6 μg/ml and 14.2 ± 1.7 μg/ml respectively, with p value of 0.66. The corresponding mean values of phenytoin drug metabolite levels saliva were 1.42 ± 0.34 μg/ml and 1.38 ± 0.37 μg/ml with p value of 0.75. Correlation of phenytoin drug metabolite to PI, GI, and OHI in both the groups did not show any statistical significance. (R values ranging from −0.229 to 0.434). Correlation between the serum and salivary drug metabolites in both the responder and non responder group also did not show any statistically significant relationship.Conclusion No correlation between the drug concentration in either the serum or saliva can be correlated to PIGO. Whole Saliva could be a useful tool in therapeutic drug monitoring of phenytoin.Clinical relevanceScientific rationale: To assess and compare the drug metabolite levels in serum and saliva of a neurologic condition where therapeutic drug concentration is of key importance to minimize the side effects. Principle finding: Saliva could be as useful as serum in deciding the drug concentration of phenytoin. And PIGO is not related drug concentrations. Practical implication: Monitoring the drug dosage is of paramount importance for the success of antiepileptic therapy as well as control of its side effects. This longitudinal study confirms that saliva could be an effective alternative to serum for monitoring drug dosage of phenytoin.